(untitled) (Innovative professional education, 2024)
The Italy experience in the introduction of public-private partnerships in professional education is analyzed. It was found that the main orientation of the reorganization here is the provision of qualifying skills per the labor market needs. Those specific mechanisms of establishing partnerships between state and private organizations in the field of professional education, which are useful for rethinking and using in modern Ukrainian realities, are highlighted.